The Relationship Between Distribution of Pharmacy Locations and The Availability of Pharmaceutical Services In Kediri City - Ismail, Hasan; Setyawan, Fidi (Open Access Health Scientific Journal, 2025)
Background: Pharmaceutical services are a vital component of the healthcare system, with pharmacies serving not only as sources of medication but also as centers for drug-related consultation. Kediri City, one of the major cities in East Java, has a population of approximately 295,230 people and an area of 63.4 km², with 156 pharmacies distributed across its regions. However, the uneven distribution of pharmacies may affect public access to pharmaceutical services. This study aimed to analyze the impact of pharmacy distribution on community access to pharmaceutical services in Kediri City.Methods: A quantitative approach was employed using data from the local Health Office, field observations, and a survey of 102 respondents across three districts.Result: The results reveal that areas with a higher number of strategically located pharmacies enjoy better access to pharmaceutical services, whereas regions with fewer pharmacies experience access barriers, such as longer travel time, limited service availability, and lower patient satisfaction.Conclusion: These findings highlight the importance of regulation and oversight in pharmacy distribution to ensure equitable access to services across all areas. Limitations of the study include a limited number of respondents, simple random sampling without stratification, and constrained observational scope. The study recommends policy development for pharmacy distribution based on regional needs to improve access and quality of pharmaceutical services in Kediri City.